Pemanfaatan Media Sosial sebagai Media Pembelajaran Pendidikan Agama Islam Berbasis Literasi Digital: Studi di SMP Al-Muttaqin - Siti Isti Arinda; Muhammad Saepul Ulum; Delis Sri Maryati (Aksioreligia, 2026)
This study aims to analyze the utilization of social media as a digital literacy-based learning medium for Islamic Religious Education (PAI) at SMP Al-Muttaqin. A qualitative descriptive approach was employed in this research. Data were collected through observation, in-depth interviews, and documentation techniques. Data analysis was carried out through data reduction, data display, and drawing conclusions. The results indicate that platforms such as YouTube, TikTok, Instagram, and WhatsApp are appropriately utilized as PAI learning tools through audio-visual content and digital interaction. The application of digital literacy is shown to assist students in critically understanding, analyzing, and verifying the accuracy of religious information. Furthermore, the use of social media enhances student engagement and comprehension in the PAI learning process. This research offers practical contributions to the development of PAI learning models that are adaptive to the digital era and reinforces religious value-based digital literacy in secondary schools.